Variation in use of procurement biopsies and its implications for discard of deceased donor kidneys recovered for transplantation. Issue 8 (12th April 2019) - Lentine, Krista L.; Naik, Abhijit S.; Schnitzler, Mark A.; Randall, Henry; Wellen, Jason R.; Kasiske, Bertram L.; Marklin, Gary; Brockmeier, Diane; Cooper, Matthew; Xiao, Huiling; Zhang, Zidong; Gaston, Robert S.; et al.
Abstract : The use of procurement biopsies in deceased donor kidney acceptance is controversial. We analyzed Scientific Registry of Transplant Recipients data (n = 59 328 allografts, 2014‐2018) to describe biopsy practices across US organ procurement organizations (OPOs) and examine relationships with discards, using hierarchical modeling to account for OPO and donor factors. Median odds ratios (MORs) provide the median of the odds that allografts with identical reported traits would be biopsied or discarded from 2 randomly drawn OPOs. Biopsies were obtained for 52.7% of kidneys. Biopsy use rose in a graded manner with kidney donor profile index (KDPI). Biopsy rates differed significantly among OPOs (22.8% to 77.5%), even after adjustment for KDPI and other donor factors. Discard rates also varied from 6.6% to 32.1% across OPOs. After adjustment for donor factors and OPO, biopsy was associated with more than 3 times the likelihood of discard (adjusted odds ratio [95%LCL aOR95 %UCL ], 3.29 3.513.76 ). This association was most pronounced for low‐risk (KDPI <20) kidneys (aOR, 5.45 6.477.69 ), with minimal impact at KDPI >85 (aOR, 0.88 1.151.51 ). Adjusted MORs for kidney discard and biopsy were greatest for low‐risk kidneys. Reducing the rate of unnecessary biopsy and improving the accuracy of histologic assessments in higher KDPI organs may help reduce graft discard rates. Abstract : An examination of US transplant registry data demonstrates that deceased donor kidney allograft procurement biopsy practices vary widely across organ procurement organizations, and that biopsy performance is associated with a greater than threefold likelihood of discard, although the association of biopsies with discards is most pronounced for low‐risk kidneys.